Ottawa Ankle Rules and their association with ligamentous or chondral injuries of the ankle: a prospective observational study - Dinato, Mauro César Mattos; Martinez Duarte, Marianyi Paola; Viana Pereira Filho, Miguel; de Faria Freitas, Marcio; Sato, Gsutavo Eiji Nodu; Donato Baptista, Andre; Gonçalves Pagnano, Rodrigo; Ferraz Ferreira, Gabriel (Journal of the Foot & Ankle, 2025)
Objective: Evaluate the association between the Ottawa Ankle Rules (OAR) and the presence of ligamentous and chondral injuries identified on magnetic resonance imaging (MRI). Methods: A prospective observational study was conducted in 48 patients who underwent clinical evaluation using the OAR with subsequent MRI assessment. Variables analyzed included patient age, gender, laterality, and presence of ligamentous or chondral injuries. Statistical analyses were performed using the Shapiro-Wilk test for normality, Student’s t-test for age comparisons, and Pearson’s chi-square test to assess associations between categorical variables. Results: Mean age of patients was 41.06 years, ranging from 15 years to 82 years. Groups with positive and negative OAR results were homogeneous regarding age (p = 0.29), gender (p = 0.42), and laterality (p = 0.09). No significant association was found between a positive OAR and the presence of ligamentous injuries (p = 0.42) or chondral injuries (p = 0.83) on MRI. Conclusion: The OAR were not associated with ligamentous or chondral injuries identified on MRI, suggesting their limitations in predicting these specific findings. Further studies are needed to develop a more accurate predictive model incorporating clinical and imaging parameters. Level of Evidence IV; Prospective Observational; Case Series